The Effective Role of Internal Factors on Reconstructing Telecom Companies: The Case of Yemen Telecom - Mohammed Ali Ahmed Al-Sharafi (Sustainability, 2021)
This paper highlights the effects of internal factors on restructuring state-owned enterprises (SOEs) and investigates how these factors have positive or negative effects on applying a new structure in SOEs companies. Yemen Telecom (YT) is an example of an SOE company that belongs to the government and has a social responsibility. By following scientific theories related to research’s factors, we tried to tie our hypotheses to the theories applied to make our factors near reality and be applicable in the future. Methods: In this study, we used empirical research by making an investigation by distributing a questionnaire amongst people who have a relationship with Yemen Telecom. Moreover, the structural equation model (SEM) was used in the current study as the statistical technique for the collected data. Results: The results of this study indicate that illiteracy in using the computer (IIUC) and applying the IT Software (AIS) has adverse effects on reconstructing telecom companies (RTC); also, AIS has a causality effect between illiteracy in using computers (IIUC) and RTC. Moreover, support from top management (SFTM), infrastructure (INF), and efficiency and effectiveness of managerial operations (EaE) have positive effects on RTC. Conclusions: This study concluded that IIUC, TMS, INF, and EaE have an apparent effect on RTC, and AIS has a causality effect between IIUC and RTC. Moreover, the study declares that there is less significance between AIS and RTC.